2021
DOI: 10.1002/bit.27762
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of microparticle addition on mycelial morphology, natural yellow pigments productivity, and key genes regulation in submerged fermentation of Monascus purpureus

Abstract: Morphology plays an important role in fungal fermentation and secondary metabolites biosynthesis. One novel technique, microparticle-enhanced cultivation was successfully utilized to control the morphology of Monascus purpureus precisely and enhance the yield of yellow pigments. The production of yellow pigments increased to 554.2 U/ml when 4 g/L 5000 mesh talc added at 24 h. Field emission scanning electron microscope observation indicated that the actual effect depends on the properties of microparticle. Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…However, these two indexes showed a decreasing trend when the talc concentration reached 20 g/L. This phenomenon is similar to a study on the production of natural yellow pigments in Monascus purpureus using morphological regulation of mycelial pellets based on microparticles [ 23 ]. This result clearly indicated that macrofungi have complex responses to the type and dosage of exogenous additives (even inert substances) during liquid fermentation.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, these two indexes showed a decreasing trend when the talc concentration reached 20 g/L. This phenomenon is similar to a study on the production of natural yellow pigments in Monascus purpureus using morphological regulation of mycelial pellets based on microparticles [ 23 ]. This result clearly indicated that macrofungi have complex responses to the type and dosage of exogenous additives (even inert substances) during liquid fermentation.…”
Section: Resultssupporting
confidence: 87%
“…SEM observation of mycelial pellet morphology was conducted in analogy to a reported method for the mycelial pellets of Monascus purpureus [ 23 ]. The surface of the sample was sputtered with a thin layer of gold, and the surface shape was observed by a field emission scanning electron microscope (SU8010 Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some mineral salts such as KH 2 PO 4 , MgSO 4 , and FeSO 4 , no matter whether added alone or together to the broth, all effectively increased the red pigment production, even reaching an increase of 102% when added together 30 . Supplementation of 4 g/L 5000 mesh talc to the broth improved the yellow pigment production by 2.13‐fold compared with the control group 31 . Research has shown that these additives, including tyrosol and mineral salts as well as talc, can all up‐regulate the expression of the relative pigment synthesis genes or activated critical enzymes responsible for pigment formation, such as esterase 12 .…”
Section: Strategies To Improve the Monascus Pigment Productionmentioning
confidence: 97%
“…For example, the addition of 3% (v/v) ethanol and 35 g/L NaCl both effectively stimulated mycelial virgation accompanied by 1.59‐ and 1.40‐fold increases in pigment production, respectively 32,33 . In addition, the increased fluidity of the cell membrane also enhanced the pigment yield 31,34,35 . Liu et al .…”
Section: Strategies To Improve the Monascus Pigment Productionmentioning
confidence: 99%
“…The results of study showed that the maximum yellow pigment production was obtained with talcum (554.2 U/mL). Moreover, it was also reported that morphological changes, such as like including smaller mycelial size, rougher hyphae, and decreased cell integrity, were induced by talc addition [60]. On the other hand, Huang et al [74] was evaluated sodium starch octenyl succinate (OSA-SNa) microparticle combined with Triton X-100 for improving of Monascus red pigments.…”
Section: Pigmentsmentioning
confidence: 99%